Sargachromenol from Sargassum micracanthum Inhibits the Lipopolysaccharide-Induced Production of Inflammatory Mediators in RAW 264.7 Macrophages - Eun-Jin Yang; Young Min Ham; Kyong-Wol Yang; Nam Ho Lee; Chang-Gu Hyun (The Scientific World Journal)
During our ongoing screening program designed to determine the anti-inflammatory potential of natural compounds, we isolated sargachromenol from Sargassum micracanthum. In the present study, we investigated the anti-inflammatory effects of sargachromenol on lipopolysaccharide (LPS)-induced inflammation in murine RAW 264.7 macrophage cells and the underlying mechanisms. Sargachromenol significantly inhibited the LPS-induced production of nitric oxide (NO) and prostaglandin E2 (PGE2) in a dose-dependent manner. It also significantly inhibited the protein expression of inducible NO synthase (iNOS) and cyclooxygenase-2 (COX-2) in a dose-dependent manner in LPS-stimulated macrophage cells. Further analyses showed that sargachromenol decreased the cytoplasmic loss of inhibitor κBα (IκBα) protein. These results suggest that sargachromenol may exert its anti-inflammatory effects on LPS-stimulated macrophage cells by inhibiting the activation of the NF-κB signaling pathway. In conclusion, to our knowledge, this is the first study to show that sargachromenol isolated from S. micracanthum has an effective anti-inflammatory activity. Therefore, sargachromenol might be useful for cosmetic, food, or medical applications requiring anti-inflammatory properties.